Hypertension after renal transplantation in patients treated with cyclosporin and azathioprine. Issue 3 (March 1990) - Gordjani, N; Offner, G; Hoyer, P F; Brodehl, J
Abstract : The incidence of hypertension was sought in 102 children who had undergone renal transplantation. Fifty five were being treated with cyclosporin and 47 with azathioprine, and they were followed up for a maximum of five years. After one year 35 of those receiving cyclosporin (64%) and 34 of those receiving azathioprine (72%) were hypertensive; after five years the figures were 5/6 (83%) and 25/35 (71%), respectively. Recipients of grafts from living related donors had a lower incidence of hypertension than recipients of cadaveric grafts. The incidence of hypertension was higher in patients with acquired original kidney disease than in children with congenital or familial diseases. In both groups creatinine clearance and the frequency of acute rejection episodes did not differ between normotensive and hypertensive patients. When the lowest concentrations of cyclosporin in whole blood were more than 400 ng/ml the incidence of hypertension one year after transplantation was higher. The incidence of hypertension after renal transplantation in children is higher than that reported in adults. Acquired original disease, transplantation of cadaveric grafts, and nephrotoxicity of cyclosporin are all contributory factors.